Event‐triggered coordinated attitude control for satellite formation under switching topology. Issue 2 (21st April 2020) - Guo, Fengzhi; Zhang, Tingting; Zhang, Fan; Gao, Lei; Wang, Zhipeng; Zhang, Shijie
Abstract : Event‐triggered coordinated attitude control problem for satellite formation under switching topology is investigated in this article. First, triggering function with state error is designed to adjust update period of controller. Event is triggered, state information is sampled, and controller is updated if and only if triggering condition is satisfied, while controller in nontriggering time uses state information of triggering time. Then, in the existence of model uncertainties, distributed adaptive attitude controller based on event‐triggered strategy is proposed for satellite formation with leader‐follower architecture. Under directed switching graph, formation system is proved to be asymptotical convergence by Lyapunov stability theory, and inter‐event time interval is given to avoid Zeno behavior. At last, simulation results show that the proposed event‐triggered adaptive attitude controller can reduce execution frequency of control tasks, as well as ensure control performance of cluster system. Abstract : An event‐triggered coordinated attitude control algorithm is proposed for satellite formation under directed switching topology. Reduce the execution frequency of control task, meanwhile ensure the similar control performance with the traditional one. Convergence time of formation system and execution frequency of control action are influenced by switching topology.